Despite Genetic Iron Overload, Hfe‐Hemochromatosis Mice Do Not Show Bone Loss. (26th July 2019) - Wagner, Alessa; Alan, Betül; Yilmaz, Dilay; Ahmad, Mubashir; Liu, Peng; Tangudu, Naveen Kumar; Tuckermann, Jan P; Vujic Spasic, Maja
ABSTRACT: One of the most prevalent genetic iron overload disorders in Caucasians is caused by mutations in the HFE gene. Both HFE patients and Hfe ‐mouse models develop a progressive accumulation of iron in the parenchymal cells of various tissues, eventually resulting in liver cirrhosis, hepatocellular carcinoma, cardiomyopathies, hypogonadism, and other pathologies. Clinical data and preclinical models have brought considerable attention to the correlation between iron overload and the development of osteoporosis in HFE/Hfe hemochromatosis. Our study critically challenges this concept. We show that systemic iron overload, at the degree present in Hfe −/− mice, does not associate with the microarchitecture impairment of long bones, thus excluding a negative effect of iron overload on bone integrity. We further reveal that Hfe actions in osteoblasts and osteoclasts are dispensable for the maintenance of bone and iron homeostasis in mice under steady‐state conditions. We conclude that, despite systemic iron overload, Hfe −/− mice present normal physiological bone homeostasis. © 2019 The Authors. JBMR Plus in published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.